Podatek od czynności cywilnoprawnych a przepisy o gospodarce nieruchomościami - Babiarz, Stefan (Kwartalnik Prawa Podatkowego, 2015)
Interpretation of Article 2 subsection 1 item g) of the Act on tax on civil law transactions suggests that for the application of exclusion from the scope of the Act on tax on civil law transactions, it will be sufficient if the case is subject to regulations on the management of real properties, and the civil law transaction itself does not necessarily have to be specified in this Act. Moreover, the term used in this Article – “regulations on the management of real properties” – may not be limited only to the regulations of the sole Act on the management of real properties and acts indicated in its Article 2 subsections 1–13. It also needs to be shown that the regulations of a given act govern the management of real properties owned by the State Treasury or local government units, and the civil law transaction included in the scope of Article 1 of the Act on tax on civil law transactions was the subject matter of such Act.